2014
DOI: 10.1186/preaccept-1569742861123837
|View full text |Cite
|
Sign up to set email alerts
|

Comparative entomological study on ecology and behaviour of Anopheles mosquitoes in highland and lowland localities of Derashe District, southern Ethiopia

Abstract: Background: Change in climatic and socio-economic situations is paving the way for the spread of malaria in highland areas which were generally known to be malaria free. Despite this, information regarding highland malaria transmission is scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…This result is consistent with the results found by Caminade et al [ 11 ], in which they showed that P. falciparum would expand its current distribution towards areas situated in greater latitudes and altitudes, if the temperatures in those areas increased. Additional supporting evidences were found in highland ecosystems in where parasites and vectors had expanded their geographic distributions towards malaria-free highlands because of climatic and socio-economic changes [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 92%
“…This result is consistent with the results found by Caminade et al [ 11 ], in which they showed that P. falciparum would expand its current distribution towards areas situated in greater latitudes and altitudes, if the temperatures in those areas increased. Additional supporting evidences were found in highland ecosystems in where parasites and vectors had expanded their geographic distributions towards malaria-free highlands because of climatic and socio-economic changes [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 92%
“…In line with this study, An. gambiae was found to be the most abundant species in a wide variety of sites in Mbita, western Kenya [40], in stream edges in Eritrea [9] and southern Ethiopia [41] and along river edges during the dry season and short rainy season in the Rift Valley in central Ethiopia [24].…”
Section: Discussionmentioning
confidence: 99%
“…The number of reported human infections with P. falciparum is increasing in tropical highland regions across the globe, for example, in Eastern Africa, Nepal, and Colombia . Competent malaria vectors have also recently been found at higher altitudes …”
Section: Recent Studiesmentioning
confidence: 99%
“…43 Competent malaria vectors have also recently been found at higher altitudes. 47,49,[51][52][53][54] This has serious implications for indigenous highland human populations that usually lack protective immunity and are more vulnerable to severe malaria morbidity and mortality. The extraordinary biological complexity of the malaria parasite has hindered the development of effective vaccines, even though it is well known that transmission-blocking antiparasite immune responses exist.…”
Section: Malariamentioning
confidence: 99%